2022
DOI: 10.1007/s12144-022-03502-3
|View full text |Cite
|
Sign up to set email alerts
|

The longitudinal association between Perceived Stress, PTSD Symptoms, and Post-Traumatic Growth during the COVID-19 Pandemic: the role of coping strategies and psychological inflexibility

Abstract: The present study investigates the mediating roles of psychological inflexibility and differential coping strategies on perceived stress and post-traumatic symptoms and growth in the context of COVID-19. Study one recruited 662 participants (54.8% women; Mage = 40.64 years, SD = 13.04) who completed a cross-sectional questionnaire. It was proposed that orientation to the problem, avoidance strategies, psychological inflexibility, and positive attitude were mediators for the positive association between perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 84 publications
0
11
0
Order By: Relevance
“…The Coronavirus Disease 2019 (COVID-19) Pandemic, caused by the SARS-CoV-2 virus was first reported in December 2019 in Wuhan China and subsequently documented in more than 210 countries around the world, represented an emergency for international public health [ 1 ] of both the general population [ 2 , 3 , 4 ] and vulnerable groups [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Coronavirus Disease 2019 (COVID-19) Pandemic, caused by the SARS-CoV-2 virus was first reported in December 2019 in Wuhan China and subsequently documented in more than 210 countries around the world, represented an emergency for international public health [ 1 ] of both the general population [ 2 , 3 , 4 ] and vulnerable groups [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative research shows that many patients show obvious changes in different themes of post-traumatic growth such as coping strategies, existing growth, lessons learned from disease, new opportunities, and social growth after infection with COVID-19 ( 15 ). As a negative psychological reaction, PTSD, depression, anxiety and positive psychological results of PTG not only exist in the normal population under the background of COVID-19 ( 16 , 17 ), but also exist in COVID-19 patients ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…That is, consistent with post-trauma processing theories and the inverse of the psychological flexibility model, people with higher PTS and greater avoidance of aversive trauma-related thoughts, feelings, and images, reported the lowest levels of PTG and meaning in life ( Kashdan & Kane, 2011 ). Only two studies have examined the relationship between psychological inflexibility and PTG during the pandemic ( Bruno et al, 2022 ; Yildiz, 2021 ). Bruno et al (2020) found that psychological inflexibility longitudinally predicted higher PTS and lower PTG one year after the first Italian lockdown.…”
Section: Introductionmentioning
confidence: 99%